2020
DOI: 10.3390/microorganisms8060830
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Performance of Several Lachancea thermotolerans Strains for pH Control in White Wines from Warm Areas

Abstract: In the current scenario of climatic warming, the over-ripening of grapes increases the sugar content, producing flat and alcoholic wines with low acidity, high pH and low freshness. Additionally, a high pH makes wines more chemically and microbiologically unstable, requiring a higher sulphite content for preservation. Some strains of Lachancea thermotolerans can naturally lower the pH of wine by producing lactic acid from sugars; this pH reduction can reach 0.5 units. The industrial performance of four selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 54 publications
(97 reference statements)
5
47
0
Order By: Relevance
“…In reference to esters, it has been demonstrated that their production is closely related to the amount of yeast assimilated nitrogen (YAN) available in the must but, depending on the yeast characteristics, their production might increase or decrease with increased levels of YAN ( Carrau et al, 2008 ). The levels of ethyl acetate, with pleasant fruity aromas when the concentration is under 60 mg/L ( Medina-Trujillo et al, 2016 ) or varnish aromas when the concentration is higher, were similar to those observed in other recently published articles in which Lt was also used, with an ethyl acetate production of about 15–25 mg/L ( Canonico et al, 2019 ; Vaquero et al, 2020 ). In contrast, higher concentrations have also been obtained in previous works ( Morata et al, 2019b ; Vaquero et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In reference to esters, it has been demonstrated that their production is closely related to the amount of yeast assimilated nitrogen (YAN) available in the must but, depending on the yeast characteristics, their production might increase or decrease with increased levels of YAN ( Carrau et al, 2008 ). The levels of ethyl acetate, with pleasant fruity aromas when the concentration is under 60 mg/L ( Medina-Trujillo et al, 2016 ) or varnish aromas when the concentration is higher, were similar to those observed in other recently published articles in which Lt was also used, with an ethyl acetate production of about 15–25 mg/L ( Canonico et al, 2019 ; Vaquero et al, 2020 ). In contrast, higher concentrations have also been obtained in previous works ( Morata et al, 2019b ; Vaquero et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…It should also be noted that the Lt yeast is capable of producing large amounts of lactic acid depending on different factors ( Binati et al, 2019 ; Vaquero et al, 2020 ). The greatest amount of lactic acid was produced around day 6, as shown in previous studies ( Morata et al, 2019b ; Vaquero et al, 2020 ). It is worth noting the great synergy between the Lt + Mp ternary co-inoculation yeast for lactic acid production and, in contrast, the low production with the ternary co-inoculation of Lt + Hv, possibly due to inhibition or lack of nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations